A Case of Systemic Lupus Erythematosus with Severe Jaundice - Ferdous, Nira; Ghosh, Jhumur; Islam, Md Nazrul (Journal of Medicine, 2022)
Abnormal liver tests are common (60%) in some point of Systemic Lupus Erythematosus (SLE) illness. In rare cases, severe cholestasis may invite diagnostic dilemma. Here we reported a 48-years-old female SLE patient with severe cholestasis (serum bilirubin 37mg/dl) and her management in a financial constrain situation. J MEDICINE 2022; 23: 162-164